The ability of different curcumine solutions on reducing Candida albicans bio-film activity on acrylic resin denture base material - Nagham H. Kassab; Eman A. Mustafa; Maha T. Al-Saffar (University of Mosul, College of Dentistry, 2007)
Aims: To measure candidal biofilm activity using pH changes of stomastat, to evaluate the effect of different types of curcumine solution on Candida albicans biofilm that attached on acrylic resin denture base material (A.R.D.B.M.) and the correlation of initial number of yeasts inoculated with the pH value of stomastat after 24 hours incubation period. Materials and Methods: In general, the number of acrylic resin samples that had been used in this study was 20 samples. Curcumine solution had been dissolved in three different solvents, those were ethanol, viscous (glycerine), and sterile distilled water, while cholrhexidine (CHX) alone used as a control negative and distilled water used as a control positive. The diameter of inhibition zone for the different curcumine solution had been measured and compared with control (-ve, and +ve); the biofilm activity of Candida albicans on A.R.D.B.M. was measured by a new method using pH change of stomastat. Results: Demonstrated that the ability of curcumine solution to decrease fungal biofilm activity on A.R.D.B.M varied depending upon the type of solvent in which the solution had been dissolved, and ethanolic solution (50%) was the most effective in reducing biofilm activity of C. albicans on A.R.D.B.M. when compared with CHX solution which is the most commercially used solution as denture cleanser. Conclusion: The ethanolic solution of Curcumine can be used in prosthetic dentistry as a new denture cleansing agent.